The rise and fall of the European constitution - Barber, N. W. (Nicholas William); Cahill, Maria; Ekins, Richard (Modern studies in European law, 2019)
"The rejection of the Constitutional Treaty brought forward the momentum of ever more European integration to an abrupt halt. This collection brings together some of the leading EU constitutional scholars to comment, with the benefit of hindsight, on the significance of that rejection and how it impacted on post 2003 developments. It examines why the member states chose to reject the movement towards a federal state. It also asks why the Treaty which had support from European lawyers, failed to enthuse European citizens. This probing and rigorous account will provide answers to these often asked questions"--